PENGARUH LINGKUNGAN KERJA NON FISIK TERHADAP KINERJA (Studi Pada Pengrajin Sewel Cinta, Socah) - Veni Indriastutik; Iriani Ismail (Management Department of Economics and Business Of Trunojoyo Madura University, 2022)
Socah Village is located in Socah District, Bangkalan Regency. Housewives in Socah Village are very productive because so many home industries are developing, especially the production of snacks. One of them is Sewel. The advantages of Sewel Cinta are tasty with the addition of chili paste and peanuts. To achieve high employees performance, a non-physical work environment is needed. The purpose of this study was to determine the effect of the Non-Physical Work Environment on the Employees Performance. It uses a quantitative approach, with the entire population as respondents as many as 25 employees. Using the multiple linear regression analysis, the results showed that: 1) Supervision (X1) has a positive and significant effect on employees performance (Y). 2) Work Atmosphere (X2) has a positive and significant effect on employees performance (Y). 3) Reward System (X3) has a positive and significant effect on employees.. 4) Good Treatment (X4) has a positive and significant effect on employees performance (Y).. 5) Safety (X5) has a positive and significant effect on employees performance (Y 6) Supervision (X1), Work Atmosphere (X2), Reward System (X3), Good Treatment (X4), and Safety (X5) have a simultaneous effect on employees performance (Y).